Chorea associated with nonketotic hyperglycemia: A case report with atypical imaging changes. Issue 45 (November 2017) - Chang, Xianchao; Hong, Wenke; Yu, Hu; Yao, Yindan
Abstract: Introduction: This is a unique case of nonketotic hyperglycemic (NKH) chorea in 84-year-old Asian woman. The patient had a history of type 2 diabetes mellitus more than 30 years, but had a poor control of blood sugar. She complained of acute onset of bilateral limb involuntary activities, and being easy to fall within a week. Laboratory testing disclosed hyperglycemia (669 mg/dL), glycated hemoglobin (14%), and normal ketones. The brain computed tomography scan and magnetic resonance imaging did not disclose any abnormality in the basal ganglion unlike most cases. The patient was then diagnosed with NKH chorea. Her symptoms improved quickly. Conclusions: NKH chorea with normal imaging may represent a new subtype.